What kind of bird is this? She will stop a galloping horse: an autoethnographic exploration of transnationality, motherhood, work, and education - Glushko Evans, Anna (Kansas State University, 2023)
Adult learners who are also parents are often faced with balancing several responsibilities. Many are juggling family, academics, and work. The purpose of this study is to describe my lived experiences while navigating and negotiating transnationality, motherhood, work, and education identities. By applying the social, intersectional, non-linear conceptual framework of identity development (Cerulo, 1997; Crenshaw, 1989; Hoare, 2006; Josselson; Keller & Werchan, 2006; Tajfel & Turner, 1986; Yelich Biniecki & Conceição, 2014) as a researcher, I explore my lived experiences of transnationality and becoming a mother while pursuing a doctoral degree and working full-time through the lens of feminist autoethnography (Ettorre, 2016). In addition, I also incorporate interactions with family, friends, coworkers, other students and faculty, and the world. My experience is a unique example. My aim is to share a slice of personal reality and contribute to the bigger understanding of cultural experience that may impact other students as well. The findings of this study have the potential to greatly benefit the field of adult education by providing valuable insights on how institutions can effectively attract, retain, and support students throughout their academic journeys.
Keywords: Adult learning; Autoethnography; Child rearing; Identity; Motherhood; Transnationality